Формирование здорового образа жизни в семье - Козлова, Л.И. (My University, 2013)
The article is about a healthy lifestyle in the family support. Of scale study defines a "cornerstone" of any social state - "the family - a social unit." Promoting healthy lives of citizens as a problem of national importance and national security and meet the challenges of global scale particularly actualized in contemporary Kazakhstan. Childhood - is a unique period in human life, it is the time shape health, the personality, the experience of childhood in many ways defines adult life. At the beginning of the road next to the defenseless and unsuspecting baby are the most important people in his life - the parents. Through their love,care, emotional closeness and support of the child grows and develops, he has a sense of confidence in the world and the people around him.